KARAKTERISASI FRAGMEN GEN 18S rRNA POKEA (Batissa violacea celebensis Martens, 1897) DI SUNGAI POHARA KECAMATAN SAMPARA KABUPATEN KONAWE (Characterization of 18S rRNA Gene Fragmen from Pokea (Batissa violacea celebensis Martens, 1897) in the Pohara Rive - ., Muzuni; Adi, Dwi Arinto; Syarif, Satriani (Jurnal BioWallacea, 2014)
This study aims to characterize sequences of 18S rRNA gene fragment from Pokea (Batissa violacea celebensis Martens, 1897) and its role in differentiated Pokea with other Bivalvia. The method used is a series of PCR (Polymerase Chain Reaction) reaction used to determine the sequence of 18S rRNA gene fragments Pokea. Analysis of the data using program NCBI (National Center for Biotechnology Information), Clustal X, Phydit (Phylogenetik editor), and TreeViewX for characterization 18S rRNA gene sequence to construct a phylogenetik tree of Pokea. The results showed that character of 18S rRNA gene fragments Pokea, namely: size 827 bp, including the family Corbicullidae because it has the closest kinship with Corbicula fluminea, as well as having restriction enzyme sites XhoI, PstI, BamHI, and DraI. Â  Keywords: Morphology, characterization, 18S rRNA gene, Pokea (Batissa Violacea celebensis Martens, 1897).